2022
DOI: 10.3389/fnagi.2022.988143
|View full text |Cite
|
Sign up to set email alerts
|

Integrated bioinformatics-based identification of diagnostic markers in Alzheimer disease

Abstract: Alzheimer disease (AD) is a progressive neurodegenerative disease resulting from the accumulation of extracellular amyloid beta (Aβ) and intracellular neurofibrillary tangles. There are currently no objective diagnostic measures for AD. The aim of this study was to identify potential diagnostic markers for AD and evaluate the role of immune cell infiltration in disease pathogenesis. AD expression profiling data for human hippocampus tissue (GSE48350 and GSE5281) were downloaded from the Gene Expression Omnibus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 55 publications
1
0
0
Order By: Relevance
“…Studies have shown that ATP6V1G2 as significantly regulated by DNA methylation at hub CpGs in AD ( Kim et al, 2023 ). RGS4, a regulator of G-protein signaling, has been identified as a potential biomarker for AD in multiple studies ( Zou et al, 2019 ; Chen et al, 2022 ), and this finding has been confirmed in our result as well. Although these genes exhibit consistent strong correlations in both datasets, there are some genes whose correlations show completely opposite patterns between the two datasets.…”
Section: Discussionsupporting
confidence: 89%
“…Studies have shown that ATP6V1G2 as significantly regulated by DNA methylation at hub CpGs in AD ( Kim et al, 2023 ). RGS4, a regulator of G-protein signaling, has been identified as a potential biomarker for AD in multiple studies ( Zou et al, 2019 ; Chen et al, 2022 ), and this finding has been confirmed in our result as well. Although these genes exhibit consistent strong correlations in both datasets, there are some genes whose correlations show completely opposite patterns between the two datasets.…”
Section: Discussionsupporting
confidence: 89%